2018
DOI: 10.14419/ijet.v7i2.21.12383
|View full text |Cite
|
Sign up to set email alerts
|

Digital marketing in hotel industry

Abstract: Digital marketing is the promotion of products or brands through online. In recent days the demand of digital marketing in hotels has become increasingly high with Social Media Marketing (SMM) which works with social networking sites and Search Engine Optimization (SEO) making the website to appear in search results with advertisement on Google and online magazines by search engine marketing (SEM), video marketing through you tube and websites are types of digital marketing. Searching hotels through online by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Several studies on the adoption of SM by agencies have revealed that Facebook is by far the most used SM platform; others worth mentioning are (not in order of importance): YouTube, Twitter, WhatsApp, LinkedIn, Instagram and Telegram (Sengtong et al ., 2022; Sharma et al ., 2020; Parvez et al ., 2018; Fernandes et al ., 2016; Oji et al ., 2017; Ainin et al ., 2015; Aspasia and Ourania, 2014; Fedushko and Bekesh, 2014). The various web platforms are usually adopted in parallel and their usage is not exclusive to any one of them.…”
Section: Literature Review and Research Objectivesmentioning
confidence: 99%
“…Several studies on the adoption of SM by agencies have revealed that Facebook is by far the most used SM platform; others worth mentioning are (not in order of importance): YouTube, Twitter, WhatsApp, LinkedIn, Instagram and Telegram (Sengtong et al ., 2022; Sharma et al ., 2020; Parvez et al ., 2018; Fernandes et al ., 2016; Oji et al ., 2017; Ainin et al ., 2015; Aspasia and Ourania, 2014; Fedushko and Bekesh, 2014). The various web platforms are usually adopted in parallel and their usage is not exclusive to any one of them.…”
Section: Literature Review and Research Objectivesmentioning
confidence: 99%
“…This reflects the need of the industrial hotel practitioner to apply the transition process from traditional ways to digital marketing platforms. The demand for digital marketing nowadays has increased through Social Media Marketing (SMM) which collaborated with Search Engine Optimization (SEO) and Search Engine Marketing (SEM) enhancement (Parvez et al, 2018).…”
Section: Research Problem Statementsmentioning
confidence: 99%
“…• Advertising: TV, radio, magazines, newspapers • Direct marketing: direct selling, telemarketing, and direct-response advertising through direct mail, online, various broadcast and print media. Based on this classification, Promotional video (PV) is included in the third group, Digital or internet marketing (Parvez, Moyeenudin, Arun, Anandan, & Janahan, 2018). Digital/internet marketing uses the internet in order to inform the customers about the product or service.…”
Section: Promotionmentioning
confidence: 99%
“…It is important for a hotel to have PV as it can market their products; rooms, restaurants, facilities, etc (Parvez et al, 2018). Furthermore, it can highlight the important/unique parts of the hotel.…”
Section: Promotional Videomentioning
confidence: 99%